2018
DOI: 10.1590/2237-6089-2017-0070
|View full text |Cite
|
Sign up to set email alerts
|

Subjective well-being, religiosity and anxiety: a cross-sectional study applied to a sample of Brazilian medical students

Abstract: Data in the current study corroborated the negative association between SWB and anxiety; however, in opposition to the literature, they also evidenced a negative association between SWB and IR. In addition, the present research signaled the need for creating preventive intervention programs to increase SWB through positive psychological techniques and/or to decrease anxiety by applying, for instance, cognitive-behavioral therapy paradigms and/or mindfulness techniques to medical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 44 publications
1
11
0
7
Order By: Relevance
“…Um estudo brasileiro mostrou que, entre 2001 e 2011, houve um aumento de 26,3% para 34,5% na frequência de sono de má qualidade autorreferida e de 37% para 54% de sono insuficiente 10 . Entre alunos de medicina de uma universidade pública do Nordeste, a prevalência de sono de má qualidade autorreferida foi de 50% 20 .…”
Section: Discussionunclassified
“…Um estudo brasileiro mostrou que, entre 2001 e 2011, houve um aumento de 26,3% para 34,5% na frequência de sono de má qualidade autorreferida e de 37% para 54% de sono insuficiente 10 . Entre alunos de medicina de uma universidade pública do Nordeste, a prevalência de sono de má qualidade autorreferida foi de 50% 20 .…”
Section: Discussionunclassified
“…A previous study that was conducted by the corresponding author on the SWB of medical students from the same Brazilian public university found low levels of SWB and high levels of anxious concern in the referred population [95]. Thus, emotional training based on positive psychology was elaborated.…”
Section: Discussionmentioning
confidence: 99%
“…However, literature is scarce when considering anxiety in the general Brazilian population. Recent studies reported moderate to high levels of anxiety in specific groups, such as students (Carpena et al, 2019;Machado et al, 2018), and patients with chronic diseases (Buin et al, 2020;Soler et al, 2019). Nevertheless, the predictors of anxiety may change in a pandemic situation ( € Ozdin & Bayrak € Ozdin, 2020).…”
Section: Coronavirus Disease (Covid-19mentioning
confidence: 99%